PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TEHADAP KINERJA PEGAWAI PADA BIRO TATA PEMERINTAHAN SEKRETARIAT DAERAH PROVINSI JAWA TENGAH - Mochamad Fahad; Landjar Kurniawan; Fathurrohman Fathurrohman (Journal of Public Policy and Management Review, 2013)
In every organization anywhere in the world, man plays a very important to the development and destruction of the organization. So it can be said that man is the driving force in guiding the Organization towards the achievement of objectives. The human resources of the organization has a variety of characteristics, including the Employee performance is influenced by leadership style appropriate to the maturity level of each employee and a good motivation that will lead towards the objectives of the Organization to be achieved, For performance in getting the work becomes maximum. This research was conducted to determine the influence of leadership style and motivation to Employee Performance at The Bureau Regional Secretariat of Governance of Central Java Province. In this study using sampling techniques Proposional Random Sampling, quantitative sampling in which 42 respondents. Analysis of the data used is linear regression and multiple regression. The results showed that the employees performance of Bureau Regional Secretariat of Governance of Central Java Province well that is equal to 37,7%. From the results of 18,515 F count > F table 3,3277 the leadership style (X1) has a positive and significant impact on performance (Y), results of 15,257 F count > F table 3,3277 the motivation (X2) has a positive and significant impact on performance (Y), and The amount of the influence of leadership style (X1) and motivation (X2) simultaneously to the performance (Y) of 38,8%. The results showed that there was a positive and significant relationship between Leadership Style and Motivation of Employee Performance.